Analisa Tingkat Kecacatan Bata Beton Ringan Dengan Metode Seven Tools dan FMEA Di CV. XYZ - Mojokerto - Nur Rohkma, Ais; Enny Aryanny (International Forum of Researchers and Lecturers, 2023)
CV. XYZ is a manufacturing company whose main product is lightweight concrete bricks made in various sizes. Lightweight concrete brick with a thickness of 10 cm is the product that produces the highest defects compared to other products. The resulting defects have an average of 5% where this value exceeds the company's tolerance limit of 3-4%. Based on these problems, a study was conducted to determine the level of defects of lightweight concrete bricks and to provide suggestions for improvements to reduce defects. The research was conducted using the Seven Tools method and Failure Mode and Effect Analysis (FMEA). The results showed that the defect level of Lightweight Concrete Bricks from the highest to the lowest were chipped, cracked, uncut, and dimensional defects respectively. In addition, it can be seen that the Gompal failure mode with the cause of the disassembly or sorting process is too hard to produce the highest RPN score of 245, so that the recommendations for improvement need to be prioritized first.